Pengaruh Jumlah Penduduk Miskin, IPM dan UMR Terhadap TPT di Provinsi Sumatera Utara Periode 2011 – 2020 - Muhammad Abdi; Brigita Zai; Fahmi Apriyansyah Siregar; Runggu Sihombing (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The high level of unemployment in North Sumatra is a serious challenge that requires attention and appropriate solutions, especially considering the social and economic impact it has on society. This research aims to analyze the influence of the percentage of poor people, the Human Development Index (HDI), and the Regional Minimum Wage (UMR) on the Open Unemployment Rate (TPT) in North Sumatra. This research adopts a quantitative approach using the literature study collection method. Data obtained from the Central Statistics Agency (BPS). These funds are time series data for the 2011-2020 period. Researchers applied quantitative methods in this research. Data were analyzed using multiple linear regression tests using SPSS 26 software. The multiple linear regression tests used by researchers included normality tests and hypothesis tests. According to research results, the number of poor people, the Human Development Index, and the Regional Minimum Wage together (simultaneously) influence the Open Unemployment Rate (TPT). Partially, the number of poor people has a positive and significant effect, the Human Development Index (HDI) has a negative and significant effect, and the Regional Minimum Wage (UMR) has a positive and significant effect on the open unemployment rate (TPT) in North Sumatra in 2011-2020.